2017
DOI: 10.1186/s12879-017-2887-6
|View full text |Cite
|
Sign up to set email alerts
|

The rs738409 polymorphism of the PNPLA3 gene is associated with hepatic steatosis and fibrosis in Brazilian patients with chronic hepatitis C

Abstract: BackgroundProspective studies have shown that 80% of acute hepatitis C virus (HCV) cases progress to chronic infection; approximately 10-20% of patients with these conditions will develop liver cirrhosis within 2 to 3 decades, and 1-5% will develop liver cancer. Some studies have indicated that the rs738409 polymorphism of the PNPLA3 gene is associated with steatosis and the progression of advanced fibrosis. This study assessed the contribution of the PNPLA3 rs738409 polymorphism with regard to the steatosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
2
19
0
2
Order By: Relevance
“…We assume that in these subjects, lipid accumulation in hepatocytes with subsequent steatohepatitis accelerates progression of liver fibrosis caused by the underlying liver disease which is chronic HCV infection. Indeed, coincidence of chronic HCV infection with lipid accumulation and steatohepatitis results in more rapid development of CLF in comparison with HCV-infected individuals without steatohepatitis [1216]. The hypothesis of two independent synergic processes leading to CLF (HCV infection and steatohepatitis) is further supported by Jimenez-Sousa et al [15] who demonstrated a dose dependent effect of PNPLA3 G allele on the progression of liver stiffness in HCV infected individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that in these subjects, lipid accumulation in hepatocytes with subsequent steatohepatitis accelerates progression of liver fibrosis caused by the underlying liver disease which is chronic HCV infection. Indeed, coincidence of chronic HCV infection with lipid accumulation and steatohepatitis results in more rapid development of CLF in comparison with HCV-infected individuals without steatohepatitis [1216]. The hypothesis of two independent synergic processes leading to CLF (HCV infection and steatohepatitis) is further supported by Jimenez-Sousa et al [15] who demonstrated a dose dependent effect of PNPLA3 G allele on the progression of liver stiffness in HCV infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…More than fifty studies demonstrating that the PNPLA3 rs738409 G allele is a risk factor for non-alcoholic steatohepatitis (NASH), liver cirrhosis in NASH or alcoholic liver disease have been published in the past decade [511]. The same allele was also identified as a risk factor for liver fibrosis and cirrhosis in HCV-monoinfected individuals [1216] and in those with HCV/HIV coinfection [1720] and it also turned out to be a predisposing factor of hepatocellular carcinoma (HCC) [2124]. In a recent study, the increased risk of HCC and PNPLA3 G allele was found only in alcoholic liver disease, but not in non-alcoholic fatty liver disease or viral hepatitis B and C [25].…”
Section: Introductionmentioning
confidence: 99%
“…Kruk et al [11] C.Manchiero et al [12] U.Vespasiani-Gentilucci et al [13] V.Basyte-Bacev ice et al [14] R.Margherita…”
Section: Literature Quality Evaluationmentioning
confidence: 99%
“…Despite the growing investigational experience with TM6SF2 and PNPLA3 polymorphisms in NAFLD, their role in the spectrum of liver disease by the hepatitis C virus is not yet fully defined. Also, there is little data in mixed populations, such as among Brazilians [ 28 ]. In this context, the aim of this study is to describe the prevalence of TM6SF2 and PNPLA3 polymorphisms in Brazilian patients with chronic hepatitis C naïve for antiviral therapy, and to evaluate their association with liver fibrosis, steatosis, and other components of the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%